Português como segunda língua para surdos : a escrita construída em situações de interação mediadas pela Libras - Almeida, Djair Lázaro de (2016)
This research aims to describe and analyze the process of writing in Portuguese as a second language, undertaken by deaf participants in context of interactional and dialogical workshops, from a collective rewriting work of an adventure story, reflecting on interdiscursive interactions between sign language and written Portuguese. The rewrite was placed in this work as the object of reflection on practices and discursive formations which focused on learning of deaf participants. The discussions on this theme were guided by Bakhtin assumptions from the enunciative-discursive conception of language. This design allows us to understand the subjects in their discursive constitution through social relations in which they participate, incorporating the different social voices. For this purpose the workshops were videotaped as the intention to focus dialogic aspects of the interaction between the subjects. The episodes that make up the corpus of analysis were selected from the workshops developed in the course of the years 2013 and 2014, considering the communicative context. The excerpts of the episodes whose enunciations presented significant in relation to production strategies, review and language reflection collectively were transcribed from sign language (Libras) to Portuguese writing. The data was treated from three axes of analysis: interaction between deaf peers and between educators and listeners; language skills and written evidence. The axes analyzed allowed the establishment of qualitative values of the demanding language working by deaf people in writing workshop activities. Regarding the education of deaf people, this study points to the necessity of having the Portuguese language effectively treated as a second language, where its teaching and learning process is mediated by the sign language. Thus, the spaces that support the education for this portion of the population must be organized so as to ensure the verbal interaction, through Libras, as a written language development condition.